IMPLEMENTASI KEBIJAKAN PENGEMBANGAN KAWASAN JAKABARING - Muhammad Arif Alian (UNIVERSITAS INDO GLOBAL MANDIRI, 2018)
The development of the city is a manifestation of space requirements due to the growth of population with all its activities. To meet the needs of the space to run well, it would require a regulation that was called as spatial policies. Policies for spatial development are formulated as development guideline to realize an efficient and economical land use and able to ensure all stakeholders' interests in it. In the Palembang City, the government develop Jakabaring Region which the majority of its topography is tidal marsh. Since the late 90s, this area was developed by the government in stages. From this research we can note that the process of implementation of development policies Regions Jakabaring wasn’t going well, eventually occurred was sporadically policies implementation because of inconsistencies between the comprehensive plan with the piecemeal implementation / partial. It happened because the policy that was implemented only follow the development progress. So, each available layout plan was often revised, when being not in accordance with the implementation that was carried out. And the last, the implementation of Jakabaring Region’s development policies isn’t work well because of policies implementation that have been prepared not accompanied by strong control on development.Keywords: Implementation, policy, spatial planning, development